The Influence of Competency, Work Discipline and Compensation on Employee Performance at PT. XXX - Gemina, Dwi; Sukarno, Jurhandono; Palahudin (International Journal of Managemen Analytics (IJMA), 2024)
The importance of human resources in an organization or company is to determine the success of the organization or company in achieving its goals, because whether or not a company is successful in achieving its goals really depends on the ability of its human resources or employees in carrying out the tasks given. This research aims to analyze and identify the influence of competence, work discipline and compensation on employee performance l on employee performance. Questionnaires were distributed to 74 respondents who were taken by determining the sample using a non-probability sampling method with the sampling technique used was saturated sampling. The questionnaire was tested using validity tests, reliability tests, and also classical assumption tests. The results of this test are valid, reliable, and can be used for regression data. The analytical method used in this research is a descriptive method and path analysis with a quantitative approach. The results of the research show that 1. Competency does not have a direct and positive effect on employee performance. 2. Work discipline has a direct and positive effect on employee performance. 3. Compensation has a direct and positive effect on employee performance 4. Competence, work discipline, compensation has a direct positive effect on employee performance 5. Competency has a relationship but is not positive with work discipline 6. Work discipline has a positive relationship with compensation 7. Competency has a relationship but is not positive not positive with compensation.